Haematological and Biochemical Changes Induced by Acute Chlorpyrifos exposure and A Comparative Analysis of Tissue Catalase Activity in fish Labeo rohita exposed to 40 ppm Chlorpyrifos - Varma Greeshma; Priyadarsini S Lakshmi; Vasudevan Aswathi (BIO Web of Conferences)
There is a growing concern globally regarding the usage of the organophosphate pesticide Chlorpyrefos (CP) in paddy fields, the most commonly used pesticide in India and east Asian countries, is recently reported to produce a very toxic metabolic biproduct Chlorpyrifos -oxon which is reported to cause severe neurotoxicological and endocrine disruptive effects. This research study investigates the acute toxicity of chlorpyrifos, on the haematological , biochemical and enzymological parameters in Labeo rohita selected as a marker organism . Fishes were exposed to 1/100th of its reported LD50 (a concentration of 40 ppm chlorpyrifos) for a duration of eight hours to assess the short-term impacts of the pesticide. The results revealed a significant reduction in red blood cell (RBC) count by 48.3%, haemoglobin (Hb) levels by 29.6%, and packed cell volume (PCV) by 45.45%. Conversely, serum glucose levels increased dramatically by 253%, indicating a hyperglycemic stress response. A decrease in serum total protein and a marked shift in the albumin/globulin (A/G) ratio were observed, reflecting disruptions in protein metabolism and immune response. Catalase activity was analyzed in multiple tissues: kidney, heart, liver, gills, brain, muscle, and serum and the results indicated tissue-specific variations, with serum showing the highest increase in catalase activity (746.15%), followed by heart(303.8%) and kidney(192.68%).These highlight the toxic potential of chlorpyrifos, even at relatively low exposure levels, and underscore its capacity to induce physiological and genetic alterations in aquatic organisms and alarming effects in humans by bioaccumulation.